The Philosophy of "Habis Adat Karena Mufakat": Consensus of Diversion of Pusako Tinggi in Minangkabau - Fithri, Widia; Wira, Ahmad; Hadi, Rahmad Tri (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Inheritance distribution is a crucial issue in Islamic family law, deeply rooted in custom and culture. The Minangkabau community recognizes inheritance, known as pusako tinggi, which cannot be transferred. Selling it means the loss of community wealth, resulting in the loss of Sako and Pusako. This study aims to explore the philosophy of pusako tinggi in Minangkabau and the context of its relevance. This study uses empirical legal methods with a philosophical and customary law approach. The study was conducted at the Syekh Ahmad Khatib Al-Minangkabawi Foundation in the village of Koto Tuo Balai Gurah. The selection of Koto Tuo was based on Minangkabau customs, namely salingka nagari (customs limited to one place). Data were collected through interviews and documentation. Interviews were conducted with representatives of parties who contributed to pusako tinggi. The documents described are books, articles, research reports, and all documents related to the discussion. This research applies empirical legal methods with a philosophical and customary law approach. The research was conducted at the Syekh Ahmad Khatib Al-Minangkabawi Foundation in the Koto Tuo Balai Gurah village. The research was conducted at the Sheikh Ahmad Khatib Al-Minangkabawi Foundation in Koto Tuo kenagarian Balai Gurah. The selection of Koto Tuo is based on the custom in Minangkabau of salingka nagari (customs are limited to one place).  This study found that the land is not a mere symbol but represents the existence and dignity of the civilised Minangkabau society. Pusako tinggi in Minangkabau community consensus can be transferred when dealing with crucial customary and religious interests. This also does not contradict the principle of the relationship between Islamic law and custom, but this reality shows that the Minangkabau people adhere to custom and religion.